The Effect of Welding Parameters on Static and Dynamic Behaviors of Spot Welded Ti6Al4V Sheets - Fatih, Bozkurt; Fatih, Hayati cakir; Schmidová, Eva; M R, Sunil Kumar (My University, 2020)
In this study, the traditional α-β titanium alloy Ti6Al4V sheets were joined by the resistance spot welding process (RSW). RSW method was modeled statistically and investigated experimentally by using different welding parameters. After a literature survey, possible test parameters were determined, and experimental design was made. The objective of this study is to choose the optimum spot-welding parameters in both static and dynamic loading cases. In order to validate and calibrate the developed model, preliminary experiments were carried out, then Taguchi L9 orthogonal experimental design was determined to examine the effect of different parameters that are thought to be suitable for this process. The Signal/Noise (S/N) ratio was used for the interpretation of the results in the determined experimental setup. The experimental study aims to show the responses of spot welds created with different process parameters. In this study, electrode force, welding current, and welding time parameters were determined as the control factors, and the effect of these factors on the results was found using variance analysis (ANOVA). Additionally, a characterization study was conducted on spot-welded joints. Lastly, verification tests were performed and it was determined that optimization was applied successfully. It was determined that process parameters have a significant effect on failure mode and joint strength. The highest strength is obtained in both static and dynamic conditions at the control group.
Vliv parametrů svařování na statické a dynamické chování bodových svařovaných plechů Ti6Al4V
Keywords: Ti6Al4V; dynamic strength of Ti6Al4V; dynamic tensile test; spot welding; static strength of Ti6Al4V; Taguchi; titanium alloy; Ti6Al4V; dynamická pevnost Ti6Al4V; dynamická zkouška tahem; bodové svařování; statická pevnost Ti6Al4V; Taguchi; slitina titanu